Using physical activity and sport to teach personal and social responsibility - Watson, Doris L. (Human Kinetics, 2013)
Explains how to implement a character education programme in schools or community organisations. This title contains examples of units, lessons and assessments for teaching basketball, golf, football, volleyball, team handball, tennis, yoga, fitness and adventure education.